Issues in International Migration Law. - Plender, Richard (Brill, 2015)
This lively collection presents the revised papers resulting from a conference held at the Faculty of Law of the University of Groningen under the auspices of the Groningen Centre for Law and Governance and the Department of European and Economic Law. The conference brought together scholars from a number of countries to examine a series of current issues in international migration law - a topic which continues to be of major importance worldwide. The collection aims to widen horizons in the debate and assist in achieving an understanding of the fact, often forgotten by those who prefer rheto.